(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Newcastle Disease (ND), caused by Newcastle Disease Virus (NDV), poses a significant threat to the global poultry industry, affecting thousands of avian species and causing substantial economic losses. Despite the use of vaccines such as La Sota to induce immunity, sterilizing immunity that completely prevents virus shedding has not been achieved. This study evaluated NDV shedding and body weight changes in chickens experimentally inoculated with virulent NDV (vNDV), with or without prior vaccination, and assessed transmission to contact (sentinel) birds. Cloacal swab samples were collected at different time points post-challenge (1, 7, 14, and 21 days) and analysed using the haemagglutination (HA) test. Results revealed that in unvaccinated, vNDV-inoculated chickens, the highest virus shedding occurred at day 7, followed by a significant decline at days 14 and 21, whereas in their contact birds, a slight increase in shedding was noted at days 14 and 21. In contrast, vaccinated-challenged chickens exhibited highest virus shedding at 24 hours post-challenge, with titres decreasing over time, and no virus shedding was detected in their contact birds. Across both studies, contact birds consistently showed higher body weight gains compared to inoculated or vaccinated-challenged birds. These findings highlight the effectiveness of the La Sota vaccine in reducing virus shedding and limiting transmission, though further research is needed to elucidate the molecular mechanisms underlying NDV shedding and immunity.